Предмет: Алгебра, автор: iljyas67

найти корни квадратного уравнения

x2 -5x+6 = 0
6x2 - 7x – 3 = 0
4х2 – 13х + 9 = 0
2х2 + 7х + 5 = 0
5х2 + 3х -2 = 0

Ответы

Автор ответа: alesyaperova
2

Ответ:

 {x}^{2}  - 5x + 6 = 0 \\ d = 25 - 24 = 1 \\ x1 =  \frac{5 + 1}{2}  =  \frac{6}{2}  = 3

x2 =  \frac{5 - 1}{2}  =  \frac{4}{2}  = 2

6 {x}^{2}  - 7x - 3 = 0 \\ d = 49 + 4 \times 6 \times 3 = 49 + 72  =  \\  = 121 =  {11}^{2}  \\

x1 =  \frac{7 + 11}{12}  =  \frac{18}{12}  = 1 \frac{6}{12}  = 1 \frac{1}{2}  \\ x2 =  \frac{7 - 11}{12}  =  -  \frac{4}{12}  =  -  \frac{1}{3}

4 {x}^{2}  - 13x + 9 = 0 \\ d = 169 - 4 \times 4 \times 9 = 169 - 144 =  \\  = 25 =  {5}^{2}

x1 =  \frac{13 + 5}{10}  =  \frac{18}{10}  = 1 \frac{8}{10}  = 1.8 \\ x2 =  \frac{13 - 5}{10}  =  \frac{8}{10}  = 0.8

 {2x}^{2}  + 7x + 5 = 0 \\ d = 49 - 40 = 9 =  {3}^{2}  \\ x1 =  \frac{ - 7 - 3}{4}  =  -  \frac{10}{4}  =  - 2 \frac{2}{4}  =  \\  =  - 2.5

x2 =  \frac{ - 7 + 3}{4}  =  -  \frac{4}{4}  =  - 1

5 {x}^{2}  + 3x - 2 = 0 \\ d = 9 + 40 = 49 =   {7}^{2}  \\ x1 =  \frac{ - 3 + 7}{10}  =  \frac{4}{10}  = 0.4

x2 =  \frac{ - 3 - 7}{10}  =  \frac{ - 10}{10}  =  - 1

Похожие вопросы